Participation framework for building farm households’ capacity in Chiang Mai province agri-food system - Somboon, Jureerut; Nguyen, Thi Phuoc Lai; Nitivattananon, Vilas; Winijkul, Ekbordin (Asian Journal of Agriculture and Rural Development, 2026)
Farm households are critical actors in the agri-food system; however, they frequently encounter systemic challenges, affecting their livelihood security. This study investigates farm households in Chiang Mai, Thailand, aiming to identify system components, operational patterns, and value creation across diverse farming systems. Integrated approaches, including the agri-food supply chain framework, Porter’s Value Chain Model, and profit margin calculations, were employed. The findings indicate the dominance of the single-crop cultivation system, which yielded the highest profit margins. Traditional management influences farm households to purchase inputs from retailers and heavily relies on intermediaries for sales, with limited engagement in value-adding activities. Infrastructure deficits, such as inadequate cold storage, contributed to post-harvest losses. Although mixed farming offers diversification benefits, it incurs high operational costs. These findings provide critical actionable insights for farm households and inform agri-food businesses to refine collaborations, policymakers to build resilient and effective interventions, and researchers for future studies. The data collection period, coinciding with widespread animal disease outbreaks (African swine fever, Lumpy skin disease) and a flood in the province, resulted in limited representation of livestock and freshwater fishery systems. This situational constraint was mitigated by applying a weighted proportional analysis based on the actual farm household distribution.